Formulating WH-questions in Korean adult-child conversation: ‘Subject’, ‘topic’, and ‘zero’ particle as interactional resources - Kwon, Hyun-Jung; Rim, Si-Eun; Kim, Kyu-hyun (Journal of pragmatics, 2021)
This article, from a conversation analytic perspective, explores the functions of the Korean ‘subject’ particle ka, ‘topic’ particle nun, and zero particle, as used by children for formulating WH-questions (e.g., ‘What is this-ka/nun/ø?’). Using video-recorded adult-child interactions, it describes how the three particles are deployed for organizing the information-seeking action as different types of stance-taking actions. The ka-marked WH-question is shown to be embedded in contexts where the target referent is oriented to as a ‘problem’, as revealed by the way a child speaker disjunctively solicits an adult recipient's assistance, often displaying a negatively valenced affective stance. Zero-marking, by contrast, embodies the child speaker's stance towards being congruent with the terms of the current activity, with the inquiry being made about the ‘situated relevance’ of the target referent therein. The use of the nun-marked WH-question is remedially motivated, with the child speaker's stance displayed towards enlivening/sustaining the sequence, and keeping an adult recipient involved as the interlocutor. The findings indicate that children's competence matches that of adults not only in implementing an information-seeking action, but also in organizing distinct types of stance and recipiency, through managing the three particles as interactional resources. •WH-questions used in adult-child interactions are analyzed.•Ka-marked WH-questions formulate the target referent as a ‘problem’.•Zero-marked WH-questions enquire about the ‘situated relevance’ of the target referent.•Nun-marked WH-questions organize the current action as a continuation of the prior activity.•The three types of WH-question organize mutually distinct stance-taking actions.